Electromagnetic Pulse of a Vertical Electric Dipole in the Presence of Three-Layered Region. (21st October 2015) - Cheng, D.; Gu, T. T.; Cao, P.; He, T.; Li, K.
Abstract : Approximate formulas are obtained for the electromagnetic pulses due to a delta-function current in a vertical electric dipole on the planar surface of a perfect conductor coated by a dielectric layer. The new approximated formulas for the electromagnetic field in time domain are retreated analytically and some new results are obtained. Computations and discussions are carried out for the time-domain field components radiated by a vertical electric dipole in the presence of three-layered region. It is shown that the trapped-surface-wave terms should be included in the total transient field when both the vertical electric dipole and the observation point are on or near the planar surface of the dielectric-coated earth.